Accuracy of digital versus conventional implant impressions. Issue 6 (10th April 2014) - Lee, Sang J.; Betensky, Rebecca A.; Gianneschi, Grace E.; Gallucci, German O.
Abstract: Objective: The accuracy of digital impressions greatly influences their clinical viability in implant restorations. The aim of this study was to compare the accuracy of gypsum models acquired from the conventional implant impression to digitally milled models created from direct digitalization by three‐dimensional analysis. Materials and Methods: Thirty gypsum and 30 digitally milled models, impressed directly from a reference model, were prepared. The models and reference model were scanned by a laboratory scanner, and 30 surface tessellation language datasets from each group were imported to an inspection software program. The datasets were aligned to the reference dataset by a repeated best‐fit algorithm, and 10 specified contact locations of interest were measured in mean volumetric deviations. The areas were pooled by cusps, fossae, interproximal contacts, horizontal and vertical axes of implant position and angulation. The pooled areas were statistically analysed by comparing each group to the reference model to investigate the mean volumetric deviations accounting for accuracy and standard deviations for precision. Results: Milled models from digital impressions had comparable accuracy to gypsum models from conventional impressions. However, differences in fossae and vertical displacement of the implant position from the gypsum and digitally milled models compared to the reference model exhibited statistical significance ( P < 0.001, P = 0.020, respectively). Conclusion: Milled models from digital impression are comparable to gypsum models from conventional impression.